THE EFFECT OF EVENT AND PUBLICITY TOWARDS BRAND AWARENESS ON FINANCIAL SERVICE AUTHORITY (OJK) - Iskandar, Donant Alananto; Ratna Sari, Siti Dewi Sri (Economic Faculty, Attahiriyah Islamic University, 2017)
This study aims to find out the effect of event and publicity towards brand awareness on Indonesia Financial Service Authority, usually called with its abbreviation OJK. The research background is because OJK was newly established as a financial service authority, replacing Bank Indonesia. Therefore, exploring the awareness of the people about the function of OJK is interesting to be a research subject.This method used in this study is the quantitative method with 82 samples as the questionnaire respondents. The population chosen was an OJK’s event held at LPPI and Indonesia Banking School with 122 participants. Validity, reliability, normality, multicollinearity, heteroskedasticity, correlation, determination, regression, hypothesis and ANOVA tests are used as a statistical approach in order to define the outcome of the survey. The results of this study are both event and publicity have a positive and a significant influence towards brand awareness partially and simultaneously. As the conclusion, OJK should continue its programs. On the other hand, OJK should find another public relations strategy to accelerate people awareness about the duties of OJK. Keywords: Event, Publicity, Brand Awareness